2022
DOI: 10.1186/s13287-022-03008-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteomic analysis of exosome mimetic vesicles and exosomes derived from human umbilical cord mesenchymal stem cells

Abstract: Background Exosomes derived from mesenchymal stem cells (MSCs) have shown to have effective application prospects in the medical field, but exosome yield is very low. The production of exosome mimetic vesicles (EMVs) by continuous cell extrusion leads to more EMVs than exosomes, but whether the protein compositions of MSC-derived EMVs (MSC-EMVs) and exosomes (MSC-exosomes) are substantially different remains unknown. The purpose of this study was to conduct a comprehensive proteomic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…Therefore, we confirmed that three of the classical EV protein markers (Alix, HSP90, and Flotillin-1), often used to characterize EVs [ 20 , 21 ], were expressed in FB-eNVs. In addition, cellular proteins such as GM130 and calnexin are present in FB-eNVs as the FB-eNVs are synthesized through direct cell extrusion and may contain all organelle components [ 22 ], including the Golgi apparatus and ER. Furthermore, biological cargoes (including proteins) are randomly packed into eNVs, rather than the selective packing of specific proteins in EVs [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we confirmed that three of the classical EV protein markers (Alix, HSP90, and Flotillin-1), often used to characterize EVs [ 20 , 21 ], were expressed in FB-eNVs. In addition, cellular proteins such as GM130 and calnexin are present in FB-eNVs as the FB-eNVs are synthesized through direct cell extrusion and may contain all organelle components [ 22 ], including the Golgi apparatus and ER. Furthermore, biological cargoes (including proteins) are randomly packed into eNVs, rather than the selective packing of specific proteins in EVs [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological cargoes (including proteins) are randomly packed into eNVs, rather than the selective packing of specific proteins in EVs [ 23 , 24 , 25 ]. Nonetheless, EVs and eNVs (also called EV-mimetics) have been demonstrated to have 80% similar proteomes [ 22 ]. Next, we confirmed that the generated FB-eNVs were intact/round and approximately 100 nm in diameter, and within the range of typical EVs (e.g., exosomes) [ 3 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes-related cognitive impairment is a global challenge, with epidemiological studies reporting that the incidence of dementia in diabetic patients is two to three times higher than in nondiabetic patients. Multiple mechanisms are thought to contribute to diabetes-related dementia, including abnormal glucose metabolism (e.g., hyperglycemia and hypoglycemia), abnormal insulin action (e.g., insulin deficiency and insulin resistance), vascular abnormalities, and oxidative stress in the central nervous system (86,135). The damage to hippocampal neurons and astrocytes is considered the most critical problem of cognitive impairment caused by diabetes.…”
Section: Mesenchymal Stem Cell-derived Exosomes and Cognitive Impairmentmentioning
confidence: 99%
“…Proteomic analysis of EMVs and exosomes derived from HucMSCs revealed that they share about 80% of the same protein while also containing unique proteins. EMVs and exosomes derived from HucMSCs have tissue repair ability, promoting wound healing and angiogenesis in mice (135). Future research must determine whether different MSCderived EMVs have the same therapeutic effect as exosomes and whether they can be applied to diabetes and associated complications and other diseases.…”
Section: Challenges and Prospectsmentioning
confidence: 99%
“…However, above all, the exosomes in FBS may affect the proliferation and differentiation capability of HUCMSCs. The HUCMSCs can secrete exosomes to affect many cell types in the microenvironment [ 14 , 15 ]. We expected the benefit of Exo(-)FBS on the differentiation of HUCMSCs, including no influence on HUCMSCs’ exosome secretion and maximizing self-secreted exosomes’ functionality, which may enhance the differentiation capability of HUCMSCs.…”
Section: Introductionmentioning
confidence: 99%